Responsabilidade civil ambiental do Estado por omissão administrativa - Silva, Laís Batistuta (2015)
This dissertation aims to study the omissions of the State that generate environmental degradation and the model under which occurs the consequent liability. Therefore, the current context of risk was analyzed as well as the government in the form of Environmental Rule of Law and its protection tasks that this model implies. It is also studied the evolution of environmental liability in the Brazilian legal system, and consequently the conceptualization and environmental damage classification, the explanatory theories of causation applicable. Then, reflections were made about the doctrinal classical division of State harmful acts. The issue of liability for failure to state, first with a view to generally was treated in Brazilian law, and then to analyze the possibility of state failure regarding the environmental protection tasks. The Brazilian system, the doctrines and court decisions provided the subsidies in the statement of the need for the objective responsibility allocation model in solidarity with the entrepreneur. Faced with the possibility of double burden of imputation to society through joint liability, he sought mitigation through some different treatment alternatives in execution.